Operationalizing systems thinking approach to sustain public health rehabilitation programs: a rapid review and strategic synthesis - Nafees, Zanib; AboAlfa, Mahmoud; Alkhaldi, Mohammed (Frontiers in Rehabilitation Sciences, 2025)
BackgroundPublic Health Rehabilitation Programs (PHRPs) are essential to achieving universal health coverage and disability-inclusive health systems. Despite their importance, sustainability is threatened by demographic pressures, funding variability, and weak system integration. Systems Thinking (ST) provides a structured paradigm to address complexity, identify key leverage points, and embed adaptive capabilities for longer-term program survival. Our aim was to summarise global applications of ST in PHRPs and identify mechanisms that most effectively contribute to sustainability.MethodsWe conducted a rapid review of peer-reviewed literature and global case studies published between 2010 and 2025. The short timeframe was intentionally selected to provide timely, policy-relevant insights while laying the groundwork for more extensive future reviews. Searches in PubMed, Scopus, and WHO repositories identified studies applying ST to sustain PHRPs. Data were thematically synthesized using the WHO 10-step ST framework and the Systems Thinking for Health (ST4H) model.ResultsSix studies from six countries were included. Three mechanisms emerged: (1) Feedback Loops & Adaptive Learning, (2) Stakeholder Engagement & Systems Mapping, and (3) Strategic Leverage Points. Examples from diverse contexts, especially low- and middle-income countries such as Brazil, India, South Africa, and Jordan, demonstrated improved service integration, resilience, and reach.ConclusionST offers a robust framework for addressing persistent sustainability challenges in PHRPs. Embedding ST early in program design, supported by cross-sector engagement, systems literacy, and strong governance, enhances adaptability, equity, and efficiency. This rapid review provides actionable evidence for policymakers and practitioners, while also underscoring the need for context-specific sustainability metrics and broader scoping or systematic reviews to deepen and expand the evidence base.